PENGARUH MOTIVASI WISATAWAN TERHADAP MINAT BERKUNJUNG KE MUSEUM LAYANG-LAYANG INDONESIA - Medelyne Rhees Christo Kusnadi; Antonius Rizki Krisnadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Indonesia Kite Museum is a thematic cultural tourism destination located in Cilandak, South Jakarta, housing a collection of more than 600 kites from across the Indonesian archipelago and various countries. Despite its high educational and cultural value, the museum has experienced unstable visitor fluctuations, including a 10.56% decline in 2024. This phenomenon reflects a gap between the museum's potential and its actual visitation rate, warranting further examination through the lens of tourist motivation. This study aims to analyze the influence of tourist motivation—measured through push factors (educational, recreational, nostalgia, and family/social motivation) and pull factors (collection uniqueness, interactive activities, cultural and educational value, and physical environment appeal)—on visit intention to the Indonesia Kite Museum, both partially and simultaneously. A quantitative approach with descriptive design was employed. Data were collected via a Likert 1–5 scale questionnaire distributed to 100 respondents from the Jabodetabek area using purposive sampling. Data were analyzed using validity, reliability, normality, and heteroscedasticity tests, along with T-test, F-test, simple linear regression, and coefficient of determination using SPSS. The results indicate that both push and pull factors significantly influence visit intention, both partially and simultaneously. The coefficient of determination (R Square = 0.681) shows that tourist motivation accounts for 68.1% of the variation in visit intention, while the remaining 31.9% is influenced by other factors such as accessibility, facilities, and social media. This study concludes that tourist motivation is a strong predictor of visit intention to the Indonesia Kite Museum. The museum is advised to strengthen interactive educational programs, enhance content-based digital promotion, and improve supporting facilities to attract more visitors, particularly younger generations. Future research is encouraged to expand variables and employ mixed methods for a more comprehensive understanding of tourist behavior at thematic museums.